We have to find the value of lim x--> 90[ (1- sin x)/(cos x)^2]

substituting x = 90 degrees, we get the indeterminate form 0/0, so we can use l'Hopital's rule and substitute the numerator and denominator by their derivatives.

=> lim x->90 [ (- cos x)/ (-2 cos x...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find the value of lim x--> 90[ (1- sin x)/(cos x)^2]

substituting x = 90 degrees, we get the indeterminate form 0/0, so we can use l'Hopital's rule and substitute the numerator and denominator by their derivatives.

=> lim x->90 [ (- cos x)/ (-2 cos x * sin x)]

=> lim x->90 [ 1/ (2 sin x)]

substitute x = 90

=> 1/ 2

**The required value of lim x--> 90[ (1- sin x)/(cos x)^2] is (1/2).**